PERAN MODEL KEPEMIMPINAN TRANSFORMASIONAL DALAM KESIAPAN BERUBAH KARYAWAN TERHADAP EFEKTIVITAS KINERJA KARYAWAN - Fransisco, Fransisco; Sutikno, Arron Yonas; Adriana, Erica (APPS Publications, 2023)
This study aims to analyze the role of the transformational leadership model in increasing the readiness to change employees and the effectiveness of employee performance in a company. Transformational leadership is a leadership style that focuses on developing and empowering employees, so that they contribute optimally and can reach their full potential. Transformational leadership is a leadership model that is carried out by inspiring and motivating employees with the aim that they can destroy the boundaries within themselves by exceeding their own abilities in completing their work. This can happen if there are signs, namely: giving ideal influence, motivating inspirationally, providing intellectual stimulation and giving individual consideration. Research has provided evidence that transformational leadership has a positive impact on the performance of employees in companies. There are several ways in transformational leadership to increase the effectiveness of employee performance, one of which is to process the handling of employees to change. Improvements in performance can occur when employees can be ready to change, because they can quickly get new ideas and challenges that can improve the performance of these employees. There are several ways to get employees ready to change. The trick is to provide a high sense of concern about the need for change. It is also necessary for a leader to convey the usefulness of the change and what the risks are if you don't make the change. Another way that can be applied is by listening to the urgency of its employees, which then the leader must be able to provide support and encouragement. This support and encouragement can be done by providing training and development to employees and rewarding them for their performance in the company. A transformational leader can make the goals of the organization quickly achieved by increasing the readiness of its employees to change. By increasing employees' readiness for change, transformational leaders can help organizations achieve their goals. So, transformational leadership is a tool that can be used to increase the effectiveness of employee performance. With us being able to understand the models and behaviors of transformational leadership, the book of Isa creates a positive work environment.